Opportunistic gillnet depredation by common bottlenose dolphins in the southwestern Gulf of Mexico: Testing the relationship with ecological, trophic, and nutritional characteristics of their prey - Chávez-Martínez, Karina; Morteo, Eduardo; Hernández-Candelario, Isabel; Herzka, Sharon Z.; Delfín-Alfonso, Chrstian A. (Frontiers in Marine Science, 2022)
Competition between fisheries and bottlenose dolphins is a globally relevant conflict given its socioeconomic and ecological implications. Understanding the factors driving the interactions between dolphins and fishery activities is key to the development of appropriate mitigation strategies. Our study aimed to assess whether these interactions are related to the ecological, trophic, and nutritional characteristics of the catch. We used 117 gillnet sets from 48 fishing trips during 2009 – 2010 and 2015 – 2019, which were classified based on the presence or absence of dolphin interactions. These interactions occurred year-round and were documented in 46.1% of the sets, with 14.5% of those showing signs of depredation. The passive acoustic predatory hypothesis, which states that fish species that generate sound are subject to a higher predation intensity by dolphins, was not supported by our data. Also, with the exception of species diversity, ecological parameters such as richness, biomass and CPUE were slightly higher, although not significant in sets with dolphin interaction. Furthermore, during 2015 – 2016, we sampled 123 organisms of 25 representative fish species in the catches and determined the whole fish isotopic composition (δ13C and δ15N), and estimated the nutritional value (i.e., lipid, protein, and energy content) of each species. Isotopic values showed no differences between net settings (with and without interaction), fish habitat, or prey type (potential prey, n= 11 species, vs. non-potential prey, n= 14). However, a preference towards fish from a certain range of thropic levels was evident. All the fish (N= 123) showed significantly higher protein values during the Rainy period, which may be attributed to their reproductive cycles and higher primary productivity. Interestingly, energy contents of the dolphins’ potential prey were also significantly higher during this period. Unexpectedly, protein and energy contents were significantly higher in the fishes caught in the sets without dolphin interaction, but only during the Dry and Windy periods, respectively. Opportunistic feeding habits are well known for bottlenose dolphins, and our results showed that “easy access” to prey will likely prompt interaction with gillnets, regardless of the species composition, biomass, seasonality, preferred habitat, sound production capacity, or nutritional value of the captured fish.